Cyclin D1 and p21 gene variants and oral squamous cell carcinoma risk and prognosis - Jović, Saša; Zeljić, Katarina; Ivković, Nemanja; Štefik, Debora; Kozomara, Ružica; Stošić, Srboljub; Šupić, Gordana (Archives of Biological Sciences, 2021)
Paper description: p21 and cyclin D1, encoded by the CDKN1A and the CCND1 genes, respectively, are important regulators of cell cycle progression and could be associated with oral cancer. Gene variants within the CDKN1A (rs1801270, rs1059234) and CCND1 (rs9344) were genotyped by real-time PCR in a group of 104 oral cancer patients and 107 healthy controls. CCND1 polymorphism rs9344 was significantly associated with increased oral cancer risk but not with its prognosis. Variant rs9344 in the CCND1 gene could be considered as a potential marker for oral cancer susceptibility and might be potentially useful for future cancer risk assessment. Abstract: Cyclin-dependent kinase inhibitor p21 (encoded by the CDKN1A gene) and cyclin D1 (encoded by the CCND1 gene) are important regulators of cell cycle progression and could have important effects in the complex process of neoplastic transformation. The current study aimed to investigate variants in CDKN1A (rs1801270, rs1059234) and CCND1 (rs9344) genes as potential risk and prognostic factors in oral squamous cell carcinoma (OSCC) patients. The study included 104 OSCC patients and 107 healthy individuals without a history of cancer. Genotypes were assessed by real-time PCR and TaqMan SNP genotyping. Significant differences in genotype distribution between OSCC cases and the control group were observed for the CCND1 rs9344 variant (p=0.017). According to the odds ratio (OR), adjusted for age and sex, the rs9344 heterozygous GA and homozygous mutated AA genotypes were associated with an increased OSCC susceptibility (OR=2.295, p=0.007; OR=2.029, p=0.037, respectively). Variants rs1801270 and rs105923 in CDKN1A were not associated with OSCC risk. There were no differences in overall survival among OSCC patients stratified by genotypes of the analyzed variants in CDKN1A and CCND1. Variant rs9344 in the CCND1 gene might be considered as a potential molecular risk factor for OSCC susceptibility but not for disease prognosis.